Interventions for the treatment of uveitic macular edema: a systematic review and meta-analysis - Karim, Rushmia (Dove Medical Press, 2013)
BACKGROUND: Uveitic macular edema is the major cause of reduced vision in eyes with uveitis. OBJECTIVES: To assess the effectiveness of interventions in the treatment of uveitic macular edema. SEARCH STRATEGY: Cochrane Central Register of Controlled Trials, Medline, and Embase. There were no language or data restrictions in the search for trials. The databases were last searched on December 1, 2011. Reference lists of included trials were searched. Archives of Ophthalmology, Ophthalmology, Retina, the British Journal of Ophthalmology, and the New England Journal of Medicine were searched for clinical trials and reviews. SELECTION CRITERIA: Participants of any age and sex with any type of uveitic macular edema were included. Early, chronic, refractory, or secondary uveitic macular edema were included. We included trials that compared any interventions of any dose and duration, including comparison with another treatment, sham treatment, or no treatment. DATA COLLECTION AND ANALYSIS: Best-corrected visual acuity and central macular thickness were the primary outcome measures. Secondary outcome data including adverse effects were collected. CONCLUSION: More results from randomized controlled trials with long follow-up periods are needed for interventions for uveitic macular edema to assist in determining the overall long-term benefit of different treatments. The only intervention with sufficiently robust randomized controlled trials for a meta-analysis was acetazolamide, which was shown to be ineffective in improving vision in eyes with uveitic macular edema, and is clinically now rarely used. Interventions showing promise in this disease include dexamethasone implants, immunomodulatory drugs and anti-vascular endothelial growth-factor agents. When macular edema has become refractory after multiple interventions, pars plana vitrectomy could be considered. The disease pathophysiology is uncertain and the course of disease unpredictable. As there are no clear guidelines from the literature, interventions should be tailored to the individual patient.